Multivariate Relation Between Advertisements, Sales, and Profits: A Study on the Indian FMCG Industry - Mahendru, Mandeep; De, Kalyan K. (Indian Journal of Marketing, 2014)
This paper builds on the existing literature by studying the linkages between advertising expenditure, sales, and profits in India. The paper takes a sample of 100 FMCG companies in India and studies their advertising expenditure and sales for the period ranging from 2001-02 to 2010-11. The study uses various tools, including mean, standard deviation, coefficient of variation, kurtosis, skewness, correlation, and regression for getting insights into the data. Econometric analysis, including auto-correlation, partial auto-correlation, augmented Dickey-Fuller test, vector auto regression, variance decomposition analysis, Johansen’s cointegration, and vector error correction model were employed to find out the bivariate relationship between the variables under reference. The paper points towards the dependency of sales revenue and profit after tax on advertising expenses besides showing an obvious impact of sales revenue on profits. The paper provides significant inputs for further studies that may focus on adding more variables such as profits and firm value and study the multivariate relationship among them.